Amyloid in dementia associated with familial FTLD: not an innocent bystander. Issue 1 (2nd January 2016) - Naasan, Georges; Rabinovici, Gil D.; Ghosh, Pia; Elofson, Jonathan D.; Miller, Bruce L.; Coppola, Giovanni; Karydas, Anna; Fong, Jamie; Perry, David; Lee, Suzee E.; Yokoyama, Jennifer S.; Seeley, William W.; et al.
Abstract : Patients with frontotemporal lobar degeneration (FTLD) can show superimposed amyloid pathology, though the impact of amyloid on the clinical presentation of FTLD is not well characterized. This cross-sectional case–control study compared clinical features, fluorodeoxyglucose-positron emission tomography metabolism and gray matter volume loss in 30 patients with familial FTLD in whom amyloid status was confirmed with autopsy or Pittsburgh compound B-PET. Compared to the amyloid-negative patients, the amyloid-positive patients performed significantly worse on several cognitive tests and showed hypometabolism and volume loss in more temporoparietal regions. Our results suggest that in FTLD amyloid positivity is associated with a more Alzheimer's disease-like pattern of neurodegeneration.